Evaluation of a new human immunodeficiency virus antigen and antibody test using light-initiated chemiluminescent assay - Li, Yijun; Jin, Fangfang; Li, Yunhui; Li, Yan; Wang, Yajie; Yang, Ximing (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThe goal of this study is to evaluate the analytical and clinical performance of a new human immunodeficiency virus antigen and antibody (HIV Ag/Ab) test using light-initiated chemiluminescent assay (LiCA®) and compare it with the well-established Architect® HIV Ag/Ab combo assay in a clinical setting.MethodsWe used banked samples and national reference controls to identify the ability to detect HIV Ag/Ab and different viral subtypes. Thirteen seroconversion panels were tested to evaluate early detection of HIV. A total of 21,042 patient samples were collected to compare the diagnostic performance of LiCA® with Architect®. Screening-reactive results were confirmed by Western blotting and nucleic acid testing.ResultsTotal imprecision was within 2.49%–6.56%. The C5–C95 interval was within −10.20%–7.67% away from C50. The limit of detection for p24 antigen was <1.00 IU/mL. Using national reference panels and banked sample pools, LiCA® successfully detected all negative and positive controls in line with the criteria, and all HIV-positive specimens containing different viral subtypes. In 13 seroconversion panels, LiCA® detected reactive results on average 5.73 days (95% CI: 3.42–8.04) after the initial RNA test results were confirmed positive, which was 1.27 days earlier (−3.75 to 1.21) compared to Architect®. Paired comparisons in 21,042 clinical patient samples demonstrated that LiCA® detected HIV Ag/Ab with a slightly better performance in sensitivity (100.00% vs. 99.65%), specificity (99.85% vs. 99.81%), negative predictive value (NPV, 100.00% vs. 99.99%), and positive predictive value (PPV, 89.84% vs. 87.85%) than Architect®. Total agreement between two assays was 99.67% with a kappa value of 0.89.ConclusionLiCA® HIV Ag/Ab is a precise and highly sensitive assay for measuring HIV-1 p24 antigen and HIV-1/2 antibodies with differentiated S/Co values of Ag/Ab. The assay is appropriate for use in the clinical routine test for the early detection of HIV.